Method for improving wear resistance of aluminum-silicon alloy based on multi-scale micro-nano ceramic particles and aluminum-silicon alloy
By introducing multi-scale micro-nano WC ceramic particles into aluminum-silicon alloys, the problems of nano-ceramic particle agglomeration and stress concentration of large-sized particles are solved, and the wear resistance, strength and plasticity of aluminum-silicon alloys are improved, which has important application value.
Patent Information
- Application Number
- CN202411900457.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
Nanocerite particles in existing aluminum alloys are prone to agglomeration and reduce mechanical properties, while large-size micron-size particles can only play a heterogeneous nucleation effect, resulting in stress concentration and reduced strength.
Multi-scale micro-nano WC ceramic particles are used as reinforcement, and WC micro-/sub-micron/nano hybrid particles of 6-8:1-3:1 are prepared by ball milling, and used as the reinforced phase of aluminum-silicon alloy. By reasonably controlling the amount of ceramic particles, the wear resistance of aluminum-silicon alloy is improved.
Through the synergistic action of multi-scale ceramic particles, the phenomenon of nanoparticle agglomeration is eliminated, and the wear resistance, tensile strength and plasticity of aluminum-silicon alloys are improved. The cost is low and it has important practical application value.
Smart Images

Figure CN119710332A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to aluminum silicon alloy technology, and in particular to a method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles and an aluminum silicon alloy. Background Art
[0002] With the rapid development of my country's transportation industry, the production concept of light weight, high strength and low cost has gradually become the core strategic goal of the transportation field. my country urgently needs more advanced, high-strength and lightweight parts materials and manufacturing technologies. Aluminum alloys occupy an important position in the development of lightweight and high-strength toughness materials with their low cost, good strength and plasticity, and corrosion resistance. Aluminum-silicon alloys have become the most widely used cast aluminum alloys in the machinery industry, especially in the automotive industry, due to their good casting properties, good corrosion resistance and medium cutting performance. At present, the strengthening and toughening treatment of aluminum alloys is to further obtain the required properties by adding a certain amount of reinforcing phases in the smelting of aluminum alloys. It is a method that saves time, is environmentally friendly and has significant effects. In recent years, the use of ceramic particles with high specific strength, high hardness, corrosion resistance and wear resistance as the reinforcing phase of the alloy has become a hot topic of current research.
[0003] When widely used nano-sized ceramic particles are added to aluminum melt, the particles that are not used as heterogeneous nucleation cores are often distributed in two ways, namely, they are pushed by the solid-liquid interface or captured by the solid-liquid interface. The particles pushed by the solid-liquid interface will be adsorbed at the front of the solid-liquid interface, hindering the growth of dendrites, thereby refining the dendrites, that is, improving the yield strength of the material by grain refinement and pinning the grain boundaries. The nanoparticles captured by the solid-liquid interface are distributed inside the grains, and through the second phase strengthening method, they hinder the slip of dislocations, thereby strengthening the alloy. In addition, smaller nanoparticles can improve the high-temperature mechanical properties of aluminum alloys because they can be pinned to the grain boundaries. However, nanoparticles also have certain problems. For example, when small particles are added to the aluminum alloy melt by external addition, they are prone to agglomeration and deteriorate the mechanical properties of the alloy. Large-sized micron-sized particles (often much larger than 1μm) can only play the role of heterogeneous nucleation, and due to their large size, they are prone to stress concentration around the particles, thereby reducing the strength of the material. Summary of the invention
[0004] The purpose of the present invention is to propose a method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles in response to the above problems. The method introduces ceramic particles containing multi-scale WC micron, WC submicron and WC nano mixed as a reinforcing agent into the aluminum silicon alloy as a reinforcing phase of the aluminum silicon alloy, and by reasonably controlling the amount of ceramic particle reinforcing agent added, the wear resistance of the aluminum silicon alloy is greatly improved.
[0005] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.
[0006] To achieve the above object, the technical solution adopted by the present invention is: a method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles, comprising the following steps:
[0007] Step 1: preparing multi-scale micro-nano WC ceramic particle reinforcement;
[0008] Step 2: Using aluminum foil to spin-coat a multi-scale micro-nano WC ceramic particle reinforcing agent to prepare a reinforcing agent wire;
[0009] Step 3, in a smelting furnace, melt the AlSi aluminum-silicon alloy into aluminum-silicon alloy liquid, add a refining agent for refining, and during the refining process, add a strengthening agent wire preheated to 773K-823K into the molten aluminum-silicon alloy liquid, followed by mechanical stirring to obtain a mixed alloy liquid;
[0010] The amount of multi-scale micro-nano WC ceramic particle reinforcement agent added is 0.1wt.% to 0.4wt.% of the aluminum-silicon alloy liquid;
[0011] Step 4: After the temperature of the mixed alloy liquid is raised to 1003K-1013K, an aluminum alloy slag remover is added, and after mechanical stirring, degassing, refining and slag removal are performed;
[0012] Step 5: Cast the refined and deslagging mixed alloy liquid into a rod-shaped aluminum alloy ingot.
[0013] Furthermore, in the multi-scale micro-nano WC ceramic particle reinforcing agent in step 1, the content ratio of WC micron, WC submicron and WC nanometer is 6-8:1-3:1, preferably 7:2:1.
[0014] Furthermore, the multi-scale micro-nano WC ceramic particle reinforcement in step one is obtained by ball milling WC particles.
[0015] Furthermore, in step 1, preparing a multi-scale micro-nano WC ceramic particle reinforcement comprises the following steps:
[0016] Step 1: Mix WC particles and Al 2 O 3 Mix the small balls and put the ball mixture into the ball mill jar;
[0017] Step 2, adding oleic acid into the ball mill, setting the ball milling parameters for ball milling;
[0018] Step 3, the ball milling speed is 400-800r / min, the ball milling time is 2-16h, and the can is opened and sampled every 2h. Finally, the ball-milled WC particles are dried and stored in a drying tank;
[0019] Step 4: perform particle size measurement and phase composition analysis on the WC particles after ball milling.
[0020] Furthermore, in step 2, the diameter of the reinforcing agent wire is 5-15 mm, preferably 10 mm.
[0021] Furthermore, the content of aluminum foil in the reinforcing agent wire in step 2 is negligible.
[0022] Furthermore, the AlSi aluminum silicon alloy in step 3 is an Al-12Si aluminum silicon alloy, and the Si content in the alloy is 12%. Unless otherwise specified in the present invention, % refers to mass percentage.
[0023] Furthermore, the preparation of aluminum-silicon alloy liquid in step three comprises the following steps:
[0024] Step a, placing the aluminum-silicon alloy Al-12Si into a crucible, and then placing it into a crucible-type resistance melting furnace, and heating it to 1013K-1033K;
[0025] Step b, after the alloy is completely melted, keep warm for 5-10 minutes;
[0026] Step c, adding a slag remover to refine and remove slag from the alloy liquid, and then keeping the temperature for 2 to 5 minutes to obtain an AlSi12 alloy liquid.
[0027] Step d: press the strengthener wire preheated to 773-823K into the molten aluminum-silicon alloy liquid with a bell jar, and perform ultrasonic stirring, and keep warm for 3-5 minutes after stirring.
[0028] Furthermore, the refining agent in step three is one or more Na salts.
[0029] Furthermore, in step three, the amount of refining agent added is 0.2-0.8wt.%, preferably 0.5wt.%, based on the mass of the aluminum-silicon alloy liquid.
[0030] Furthermore, the aluminum alloy slag cleaning agent described in step 4 is a slag cleaning agent special for aluminum alloys, specifically including fluorides, alkali metal compounds, silicates and oxidants.
[0031] Furthermore, in step 4, the amount of aluminum alloy slag remover added is 0.05-0.10wt.% of the mass of the mixed alloy liquid.
[0032] Furthermore, in step five, the mixed alloy liquid is cast into a metal mold to form a rod-shaped aluminum alloy ingot.
[0033] Furthermore, the metal mold is made of 45# steel.
[0034] Another object of the present invention is to disclose an aluminum-silicon alloy prepared by the above method.
[0035] Furthermore, the weight loss of the aluminum-silicon alloy tested according to national standards is reduced by 1.09 times, that is, the wear resistance is improved by 109%.
[0036] Furthermore, the aluminum silicon alloy contains 0.1 wt.% to 0.4 wt.% of a multi-scale micro-nano WC ceramic particle reinforcement.
[0037] Another object of the present invention is to disclose the use of aluminum silicon alloy in the fields of ships and automobiles.
[0038] The method for improving the wear resistance of aluminum-silicon alloy based on multi-scale micro-nano ceramic particles and the aluminum-silicon alloy of the present invention have the following advantages compared with the prior art:
[0039] The method provided by the present invention improves the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles, utilizes ceramic particles containing multi-scale WC micron / submicron / nano mixture as the reinforcing phase of the aluminum silicon alloy, and improves the wear resistance of the aluminum silicon alloy by reasonably controlling the addition amount of the ceramic particle reinforcement agent, while also improving the tensile strength and plasticity of the aluminum silicon alloy, with low cost, and has important significance and practical application value for the lightweight, high-strength, toughness and high wear resistance of the aluminum alloy.
[0040] When the present invention simultaneously introduces mixed-scale ceramic particles (micrometer / submicrometer + nanometer) into the aluminum-silicon alloy matrix, the particles of different scales produce a synergistic effect, which can not only eliminate the "agglomeration" phenomenon of nano-sized ceramic particles, but also give full play to the advantages of multi-scale ceramic particles, and prepare a particle-reinforced aluminum-silicon alloy material with good dispersion, super toughness and high wear resistance. The aluminum-silicon alloy has good application prospects and large-scale production potential in the fields of ships and automobiles. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The morphology of the unmilled WC particles in Example 1 of the present invention;
[0042] Figure 2 The morphology of WC particles after ball milling for 4 hours in Example 1 of the present invention;
[0043] Figure 3 The morphology of WC particles after ball milling for 8 hours in Example 1 of the present invention;
[0044] Figure 4 The morphology of WC particles after ball milling for 12 hours in Example 1 of the present invention;
[0045] Figure 5 The morphology of WC particles after ball milling for 16 hours in Example 1 of the present invention;
[0046] Figure 6 The relationship between the ball milling time and the particle size (D50) of WC particles in Example 1 of the present invention;
[0047] Figure 7 The relationship between the ball milling time and the specific surface area of the WC particles in Example 1 of the present invention;
[0048] Figure 8 The wear surface morphology of the alloy without adding WC particles in Comparative Example 1 of the present invention;
[0049] Fig. 9 The wear surface morphology of the alloy containing 0.2wt% WC particles in Example 2 of the present invention;
[0050] Fig.10 The wear surface morphology of the alloy containing 0.4wt% WC particles in Example 4 of the present invention;
[0051] Fig.11 The three-dimensional morphology of the wear surface of the alloy without adding WC particles in Comparative Example 1 of the present invention;
[0052] Fig.12 The three-dimensional morphology of the worn surface of the alloy containing 0.1wt% WC particles in Example 1 of the present invention;
[0053] Fig.13 The wear surface morphology of the alloy containing 0.2wt% WC particles in Example 2 of the present invention;
[0054] Fig.14 The wear surface morphology of the alloy containing 0.3wt% WC particles in Example 3 of the present invention;
[0055] Fig.15 The wear surface morphology of the alloy containing 0.4wt% WC particles in Example 4 of the present invention;
[0056] Fig.16 The relationship between the amount of WC powder added and the weight loss of alloy attrition in the embodiment of the present invention;
[0057] Fig.17 The relationship between the amount of WC particles added and the average friction coefficient of the alloy in the embodiment of the present invention;
[0058] Fig.18 The relationship between the amount of WC powder added and the maximum protrusion height of the wear surface of the alloy in the embodiment of the present invention;
[0059] Fig.19 This is the relationship between the amount of WC particles added and the maximum depth of the alloy wear surface in the embodiment of the present invention. DETAILED DESCRIPTION
[0060] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:
[0061] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.
[0062] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values A and B.
[0063] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.
[0064] In this specification, the word "may" means both performing a certain process and not performing a certain process.
[0065] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.
[0066] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.
[0067] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0068] Example 1
[0069] This embodiment discloses a multi-scale micro-nano WC particle reinforced AlSi12 aluminum alloy, and the preparation method thereof is as follows:
[0070] Step 1: Preparation of multi-scale WC micron / submicron / nano hybrid ceramic particles, including the following steps:
[0071] First, mix the ingredients and select Al 2 O 3 Grinding balls, 200 mesh WC particles, mix the two at a ball-to-material ratio of 3:1, and then put the ball-to-material mixture into a high-speed ball mill. The volume of the particles does not exceed 1 / 3 of the volume of the ball mill. After adding oleic acid dispersant, place the jar on a high-speed ball mill.
[0072] High-speed ball milling activation was performed at a speed of 800 r / min for 16 h, with a ball milling interval of 30 min;
[0073] The ball mill was opened and sampled every 2 hours. Finally, the WC particles after 16 hours of ball milling were dried to obtain multi-scale micro-nano WC ceramic particles.
[0074] The morphology of multi-scale micro-nano WC ceramic particles prepared with different grinding times is shown in Figure 2. Figure 1 to Figure 5 As shown, Figure 1 is the morphology of the unmilled WC particles, particle size (D 50 ) is about 100μm, with uneven sizes, irregular shapes, sharp edges, and many small particles attached to the surface. Figure 2 is the morphology of WC particles after high-speed ball milling for 4 hours, and the particle size (D 50 ) is about 5 μm, but the particles still maintain an angular and irregular appearance, and small particles still exist on the surface. Figure 3 The morphology of WC particles after high-speed ball milling for 8 hours. The particle size (D 50 ) is about 3 μm, and the overall shape gradually changes from an irregular polyhedron to a sphere, but there are still small particles attached to the large particles. Figure 4 The morphology of WC particles after high-speed ball milling for 12 hours. The particle size (D 50 ) is about 2 μm, the shape is more spherical, and there are no fine particles on the surface. Figure 5 The morphology of WC particles after high-speed ball milling for 16 hours, the particle size (D 50 ) is about 1μm, the roundness is significantly improved, the edges and corners disappear, and it presents a nearly perfect spherical state. The relationship between ball milling time and particle size (D50) of WC particles is as follows: Figure 6 As shown in Figure 2, the specific surface area of WC particles increases with the increase of ball milling time. Figure 7 As shown, the larger the specific surface area, the finer the particles.
[0075] The multi-scale micro-nano WC particles obtained by ball milling for 16 h were dried in a drying oven, wrapped with aluminum foil to form reinforcing agent wires, and then placed in a heating furnace for preheating at a temperature of 823 K.
[0076] Step 2: Heat the AlSi12 aluminum alloy ingot to 1023K in a pit-type resistance furnace to melt it into aluminum alloy liquid. After melting, add a special slag remover for aluminum alloy to refine and remove slag from the alloy liquid, and then immediately perform mechanical stirring for 4 minutes.
[0077] Step 3: Use a bell jar to press the reinforcing agent wire wrapped in step 1 into the molten aluminum-silicon alloy liquid, and the amount of reinforcing agent wire added is 0.1wt% of the weight of the aluminum liquid. Lower the ultrasonic probe to a position 50-120mm away from the liquid surface in the crucible and keep it warm for 4 minutes; after the ultrasonic probe is kept warm, turn on the ultrasonic equipment and use ultrasonic treatment for 8 minutes on the mixed alloy liquid to assist the nanoparticles to be evenly dispersed. After the ultrasonic-assisted dispersion is completed, remove the ultrasonic equipment and keep it warm for 5 minutes.
[0078] Step 4: Add 0.05wt% of aluminum alloy slag remover to the mixed alloy liquid after ultrasonic treatment, stir mechanically for 2 minutes, and then perform degassing, refining and slag removal;
[0079] Step 5: Cast the obtained aluminum-silicon alloy liquid with a strengthening agent containing ceramic particles into a metal mold to form a rod-shaped aluminum alloy ingot. The material of the metal mold is 45# steel.
[0080] The multi-scale micro-nano WC particle reinforced AlSi12 aluminum alloy obtained in this embodiment loses 1.5 mg of weight after a load of 5 N and a wear time of 30 min. There are obvious wear debris and plowing wear marks on the worn surface. The three-dimensional morphology of the worn surface is as follows: Fig.12 As shown in the figure, it can be seen that there are obvious wrinkles on the worn surface but the number is small. The maximum protrusion height of the worn surface is 478μm, which is 14.17% lower than that of the AlSi12 alloy without adding a reinforcing agent. The maximum depth of the worn surface of the sample is 1359μm, which is about 11.75% less than that of the AlSi12 alloy without adding a reinforcing agent. The average friction coefficient is 0.914COF, which is 3.9% lower than that of the AlSi12 alloy without adding a reinforcing agent. The smaller the average friction coefficient, the better the wear resistance.
[0081] Example 2
[0082] This embodiment discloses a multi-scale micro-nano WC particle reinforced AlSi12 aluminum alloy, and its preparation method is basically the same as that of Example 1, except that the amount of the reinforcing agent wire added in step three is 0.2wt% of the weight of the aluminum liquid.
[0083] The multi-scale micro-nano WC particle reinforced AlSi12 aluminum alloy obtained in this embodiment has a weight loss of 1.1 mg after a load of 5N and a wear time of 30min. The wear surface morphology is as follows: Fig. 9 As shown in the figure, there are obvious furrows on the matrix morphology, and the entire wear surface is almost flat with almost no peeling pits. The wear morphology has transformed into abrasive wear. The three-dimensional morphology of the wear surface is shown in Fig.13As shown in the figure, there are almost no wrinkles on the worn surface, and the maximum protrusion height of the worn surface is 442.9μm, which is 20.47% lower than that of the AlSi12 alloy without adding a reinforcing agent; the maximum depth of the worn surface of the sample is 1243μm, which is about 19.29% lower than that of the AlSi12 alloy without adding a reinforcing agent; the average friction coefficient is 0.883COF, which is 7.2% lower than that of the AlSi12 alloy without adding a reinforcing agent; the smaller the average friction coefficient, the better the wear resistance.
[0084] Example 3
[0085] This embodiment discloses a multi-scale micro-nano WC particle reinforced AlSi12 aluminum alloy, and its preparation method is basically the same as that of Example 1, except that the amount of the reinforcing agent wire added in step three is 0.3wt% of the weight of the aluminum liquid.
[0086] The multi-scale micro-nano WC particle reinforced AlSi12 aluminum alloy obtained in this embodiment has a weight loss of 1.8 mg after a load of 5N and a wear time of 30min. The three-dimensional morphology of the worn surface is as follows: Fig.14 As shown, there are obvious wrinkles but the number is small. The maximum protrusion height of the wear surface is 457.8μm, which is 17.79% lower than that of the AlSi12 alloy without adding a reinforcing agent. The maximum depth of the wear surface of the sample is 1414μm, which is about 8.18% lower than that of the AlSi12 alloy without adding a reinforcing agent. The average friction coefficient is 0.921COF, which is 3.2% lower than that of the AlSi12 alloy without adding a reinforcing agent. The smaller the average friction coefficient, the better the wear resistance.
[0087] Example 4
[0088] This embodiment discloses a multi-scale micro-nano WC particle reinforced AlSi12 aluminum alloy, and its preparation method is basically the same as that of Example 1, except that the amount of the reinforcing agent wire added in step three is 0.4wt% of the weight of the aluminum liquid.
[0089] The multi-scale micro-nano WC particle reinforced AlSi12 aluminum alloy obtained in this embodiment has a weight loss of 2.1 mg after a load of 5N and a wear time of 30min. The wear surface morphology of the alloy is as follows: Fig.10 As shown in Figure 2, there are some furrows on the worn surface, and the worn surface is uneven, and the wear morphology changes to abrasive wear; the three-dimensional morphology of the worn surface is as follows: Fig.15As shown, the maximum protrusion height of the wear surface is 486.8μm, which is 12.59% lower than that of the AlSi12 alloy without adding a reinforcing agent; the maximum depth of the wear surface of the sample is 1517μm, which is about 1.49% lower than that of the AlSi12 alloy without adding a reinforcing agent; the average friction coefficient is 0.936COF, which is 1.6% lower than that of the AlSi12 alloy without adding a reinforcing agent; the smaller the average friction coefficient, the better the wear resistance.
[0090] Comparative Example 1
[0091] This comparative example discloses an AlSi12 aluminum silicon alloy without adding WC particle reinforcement, and its preparation process is as follows:
[0092] (1) A certain mass of aluminum-silicon alloy is weighed in advance and placed into a crucible-type resistance melting furnace together with the crucible, and the temperature is raised to 1023K; the composition of the aluminum-silicon alloy is Al-12Si.
[0093] (2) After the alloy is completely melted and kept warm for 30 minutes, 0.10wt.% of slag remover is added to refine and remove slag from the alloy liquid. After the slag removal treatment, the alloy liquid is kept warm for 5 minutes, and then degassing, refining and slag removal are carried out. After the final slag removal treatment, the aluminum liquid can be directly cast;
[0094] (3) The obtained aluminum-silicon alloy liquid without adding ceramic particles is cast into a metal mold to form a rod-shaped aluminum alloy ingot.
[0095] In step (2), the slag cleaning agent used is composed of 35wt.% KCl and 30wt.% MgCl 2 、5wt.%AlF 3 、15wt.%Na 3 AlF 6 、5wt.%Mg 3 N 2 、5wt.%Na 2 CO 3 、5wt.%C 2 Cl 6 .
[0096] The material of the metal mold in step (3) is: 45# steel
[0097] In the comparative example, an AlSi12 alloy prepared without multi-scale micro-nano WC strengthening agent has a weight loss of 2.3 mg after a load of 5N and a wear time of 30min. Figure 8 As shown in the figure, there are obvious wear debris and obvious plowing wear marks on the friction surface, showing the morphology of spalling wear and abrasive wear. Fig.11It can be seen that there are numerous and obvious wrinkles, the maximum protrusion height of the worn surface is 556.9 μm, the maximum depth of the worn surface is 1540 μm, and the average friction coefficient is 0.951 COF.
[0098] Table 1 Wear resistance of alloys
[0099]
[0100] The data in Table 1 show that the addition of multi-scale micro-nano WC ceramic particles can effectively improve the wear resistance of the alloy. At the best wear resistance (Example 2), the weight loss of the alloy is 1.1 mg, which is 52.17% less than that of the alloy without adding particles. The average friction coefficient of the alloy is 0.883COF, which is 7.2% less than that of the alloy without adding particles, and the wear resistance is significantly improved.
[0101] Fig.16 The relationship between the amount of WC powder added and the weight loss of alloy attrition in the embodiment of the present invention; Fig.17 The relationship between the amount of WC particles added and the average friction coefficient of the alloy in the embodiment of the present invention; Fig.18 The relationship between the amount of WC powder added and the maximum protrusion height of the wear surface of the alloy in the embodiment of the present invention; Fig.19 This is the relationship between the amount of WC particles added and the maximum depth of the alloy wear surface in the embodiment of the present invention.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles, characterized in that: The following steps are involved: Step 1: preparing multi-scale micro-nano WC ceramic particle reinforcement; Step 2: Using aluminum foil to spin-coat a multi-scale micro-nano WC ceramic particle reinforcing agent to prepare a reinforcing agent wire; Step 3, in a smelting furnace, melt the AlSi aluminum-silicon alloy into aluminum-silicon alloy liquid, add a refining agent for refining, and during the refining process, add a strengthening agent wire preheated to 773K-823K into the molten aluminum-silicon alloy liquid, followed by mechanical stirring to obtain a mixed alloy liquid; The amount of multi-scale micro-nano WC ceramic particle reinforcement agent added is 0.1wt.% to 0.4wt.% of the aluminum-silicon alloy liquid; Step 4: After the temperature of the mixed alloy liquid is raised, an aluminum alloy slag remover is added, and after mechanical stirring, degassing, refining and slag removal are performed; Step 5: Cast the refined and deslagging mixed alloy liquid into a rod-shaped aluminum alloy ingot.
2. The method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles according to claim 1, characterized in that: In step 1, the content ratio of WC micron, WC submicron and WC nano in the multi-scale micro-nano WC ceramic particle reinforcing agent is 6-8:1-3:
1.
3. The method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles according to claim 1, characterized in that: The multi-scale micro-nano WC ceramic particle reinforcement described in step 1 is obtained by ball milling WC particles.
4. The method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles according to claim 1 or 3, characterized in that: In step 1, a multi-scale micro-nano WC ceramic particle reinforcement is prepared, comprising the following steps: Step 1, mix WC particles and Al2O3 balls at a ball-to-material ratio of 3:1, and put the ball-to-material mixture into a ball mill; Step 2, adding oleic acid into the ball mill, setting the ball milling parameters for ball milling; Step 3: The ball milling speed is 400-800 r / min, and the ball milling time is 2-16 h. Finally, the ball-milled WC particles are dried and stored in a drying tank.
5. The method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles according to claim 1, characterized in that: The AlSi aluminum silicon alloy described in step three is Al-12Si aluminum silicon alloy.
6. The method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles according to claim 1, characterized in that: The step 3 is to prepare the aluminum-silicon alloy liquid, comprising the following steps: Step a, placing the aluminum-silicon alloy Al-12Si into a crucible, and then placing it into a crucible-type resistance melting furnace, and heating it to 1013K-1033K; Step b, after the alloy is completely melted, keep warm for 5-10 minutes; Step c, adding a slag remover to refine and remove slag from the alloy liquid, and then keeping the temperature for 2 to 5 minutes to obtain an AlSi12 alloy liquid. Step d: press the strengthener wire preheated to 773-823K into the molten aluminum-silicon alloy liquid with a bell jar, and perform ultrasonic stirring, and keep warm for 3-5 minutes after stirring.
7. The method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles according to claim 1, characterized in that: In step 4, the amount of slag cleaning agent added is 0.05-0.10wt.% of the mass of the mixed alloy liquid.
8. The method for improving the wear resistance of aluminum silicon alloy based on multi-scale micro-nano ceramic particles according to claim 1, characterized in that: In step five, the mixed alloy liquid is cast into a metal mold to form a rod-shaped aluminum alloy ingot.
9. An aluminum-silicon alloy, characterized in that: The method is prepared by any one of claims 1 to 8.
10. Use of the aluminum-silicon alloy according to claim 9 in the fields of ships and automobiles.